การบริหารและการจัดการอุทยานมนุษย์ยุคหินใหม่ 3,380 ปี ตำบลกระเสียว อำเภอด่านช้าง จังหวัดสุพรรณบุรี - ศรีนา, รัตติยา; ศิริวรสกุล, วณิฎา (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษา 1) บริบทอุทยานมนุษย์ยุคหินใหม่ 2) ปัจจัยที่ส่งผลต่อ การบริหารและการจัดการอุทยานมนุษย์ยุคหินใหม่ 3) ผลสัมฤทธิ์ในการบริหารและการจัดการอุทยานมนุษย์ยุคหินใหม่ และ 4) แนวทางการบริหารและการจัดการอุทยานมนุษย์ยุคหินใหม่ 3,380 ปี ตำบลกระเสียว อำเภอด่านช้าง จังหวัดสุพรรณบุรี ที่มีประสิทธิภาพ เป็นการวิจัยเชิงคุณภาพ กลุ่มผู้ให้ข้อมูลสำคัญ ประกอบด้วย ผู้บริหารอุทยานมนุษย์กำนันอำเภอด่านช้าง เจ้าหน้าที่ อบต.กระเสียว และผู้เชี่ยวชาญประจำอุทยานฯ เครื่องมือที่ใช้ในการวิจัยคือ แบบสัมภาษณ์ การวิเคราะห์ข้อมูลโดยการบรรยายและการพรรณนาความและตรวจสอบข้อมูลด้วยวิธีการแบบสามเส้า ผลการวิจัยพบว่า 1. บริบทอุทยานมนุษย์ยุคหินใหม่ 3,380 ปี การบริหารและการจัดการ อยู่ในความดูแลของ สำนักสงฆ์ มีการตั้งกลุ่มเป็นคณะกรรมการ ลักษณะเป็นกันเอง ไม่มีลักษณะเชิงพาณิชย์ คณะกรรมการ ไม่ได้รับค่าตอบแทน โครงสร้างองค์กร ไม่มีการจัดทำผังองค์กรแต่อย่างใด มีการจัดแบ่งเป็นสัดเป็นส่วน แยกพื้นที่ระหว่างอุทยานและสำนักสงฆ์ การให้บริการและกิจกรรม มีการจำลองปั้นหุ่นปูนเป็นมนุษย์ ยุคหินในสมัยต่าง ๆ และจำลองบ้านพักอาศัย วิถีชีวิต การดำรงชีพ และหลุมฝังศพ อีกทั้งมีการจัดแสดง โดยนำบุคคลในท้องถิ่นมาจำลองเป็นมนุษย์ยุคหินใหม่ ลักษณะทางกายภาพ เป็นแบบเรียบ ๆ ออกแนว ชาวบ้าน ๆ จึงไม่สะดุดตาและไม่ดึงดูดเท่าที่ควร จัดแบ่งทางเดินและทำทางเดินเพื่อความสะดวกในการ เดินชมสถานที่ จัดทำป้ายอธิบายถึงมนุษย์ยุคหินต่าง ๆ มีอาคารลักษณะเป็นอาคารชั้นเดียว ชั้นบนประกอบ พิธีสงฆ์ ชั้นล่างจัดวางวัตถุโบราณ เส้นทางการเข้าถึงอุทยานที่เป็นถนนลูกรังดินแดง 2. ปัจจัยที่ส่งผลต่อสภาพการบริหารและการจัดการอุทยานมนุษย์ยุคหินใหม่ 3,380 ปี ประกอบ ไปด้วยปัจจัยภายในและปัจจัยภายนอก โดยปัจจัยภายใน ได้แก่ 1) งบประมาณ ซึ่งมาจาก 2 แหล่ง คือ 1.1) อบต.สนับสนุน และ 1.2) การบริจาค 2) บุคลากร พบว่าบุคลากรมีลักษณะดังนี้ 2.1) ขาดความรู้ เกี่ยวกับการบริหารและการจัดการอุทยาน 2.2) ขาดความเข้าใจถึงความสำคัญของการมีส่วนร่วมของชุมชน 2.3) ขาดแรงจูงใจ และ 2.4) ขาดผู้บังคับบัญชา ส่วนปัจจัยภายนอก พบว่าลักษณะของสังคมและชุมชนยัง เป็นสังคมชนบท เศรษฐกิจของชุมชนส่วนใหญ่ประกอบอาชีพการเกษตรกรรมและปศุสัตว์ กลุ่มในชุมชนมีมวลชนจัดตั้งเป็นกลุ่ม แต่ไม่มีความขัดแย้งในชุมชน 3. ผลสัมฤทธิ์ในการบริหารและการจัดการอุทยานมนุษย์ยุคหินใหม่ 3,380 ปี ผู้เข้าชมอุทยานฯ มีความประทับใจในอุทยานฯ และได้รับความสนุกสนานเพลิดเพลิน พึงพอใจต่อบรรยากาศที่มีลักษณะ เป็นธรรมชาติการมีส่วนร่วมของคนในชุมชน พบว่าเข้าร่วมในการกำหนดนโยบาย โดยเป็นคณะกรรมการ บริหาร การมีส่วนร่วมดำเนินกิจกรรม โดย 1) เข้ามาจัดกิจกรรม 2) สนับสนุนอุปกรณ์ 3) สนับสนุนพื้นที่ ให้จอดรถ และการประเมินผล ได้แก่ การเสนอแนะผ่านแบบประเมิน ผ่านการประชุม และกล่องรับความ คิดเห็น การรับประโยชน์จากการจัดกิจกรรม พบว่าประชาชนและคนในชุมชนได้รับประโยชน์ คือ อุทยาน มนุษย์ยุคหินใหม่เป็นศูนย์กลางการจัดการเรียนรู้ และความรู้สึกเป็นเจ้าของ 4. แนวทางการบริหารและการจัดการอุทยานมนุษย์ยุคหินใหม่ 3,380 ปี ที่มีประสิทธิภาพ ได้แก่ 1) ด้านการบริหารจัดการ ควรบริหารจัดการอย่างมืออาชีพ โดยการแต่งตั้งผู้มีความรู้ความสามารถทาง ด้านการบริหารพิพิธภัณฑ์เข้ามาเป็นผู้บริหาร 2) ด้านการบริการ ควรจัดให้มีการบริการแบบครบวงจร โดยนำเอาวัตถุโบราณมาจัดแสดงให้เป็นระบบ โดยการแบ่งโซนพื้นที่การจัดแสดงอย่างเป็นสากล พร้อม มีไกด์คอยให้ความรู้แก่ผู้มาเยี่ยมชม 3) ด้านงบประมาณ ควรจัดหางบประมาณเพิ่มเติม โดยจัดทำของ ที่ระลึกจำหน่าย ได้แก่ พวงกุญแจ หมวก เสื้อยืด ฆ้อนหิน เป็นต้น และ 4) ด้านการถ่ายทอดความรู้ ควร จัดให้มีการเพิ่มทักษะของเจ้าหน้าที่ให้มีความรู้ด้านการบริหารจัดการและด้านการบริการ โดยจัดการฝึก อบรมให้ความรู้เกี่ยวกับการบริหารจัดการอุทยานมนุษย์ยุคหินใหม่ และการส่งไปดูงานเกี่ยวกับพิพิธภัณฑ์ ในสถานที่อื่น ๆ คำสำคัญ : การบริหาร การจัดการ อุทยานมนุษย์ยุคหินใหม่ ABSTRACT The purposes of this research aimed to study 1) the context of Neolithic Humans Park 2) the factors affecting the administration and management of Neolithic Humans Park 3) the results of administration and management of Neolithic Humans Park and 4) the administration and management guidelines of 3,380-Year Neolithic Humans Park, Krasiao sub-district, Dan Chang district, Suphanburi province. This research employed qualitative methods. The key informants were the executive of 3,380-Year Neolithic Humans Park, Dan Chang district chief, Krasiao District Administration Organization’s officers and experts of the 3,380-Year Neolithic Humans Park. The research instrument was interview form, the collected data was analyzed by lectures and depict of monitoring data by means of triangulation. The research revealed that: 1) About the context of 3,380-Year Neolithic Humans Park, the administration and management were under the monastery’s care. The committee was informally formed without commercial purpose. The committee was unpaid. No organizational chart was found. The areas were clearly separated between the park and the monastery. For the service and activities, there were the plaster replicas of Neolithic people in different periods, houses on display, simulation of past time living and tomb on display. There was also a performance of Neolithic people performed by local people. The features of the park were not quite attractive. The pathway was constructed for convenient visit. The signs were made to give the information about the Neolithic people. The building was single-storey, Buddhist rituals took place on the upper floor while the antique items were displayed on the lower floor. The road to the Park was non-asphalt. 2) Factors affecting the administration and management of Neolithic Humans Park. For the intrinsic factor, the goal played an important role on the administration and management of the Park. The budget was from 2 sources 1) the district administration organization and 2) donation. The personnel was 1) lack of knowledge on administration and management of the Park 2) lack of understanding about the importance of community participation 3) lack of motivation 4) lack of the superordinate. For the extrinsic factor, the society and the community were up-country. The majority of people was farmers and grouped together. No conflict was found in the community. 3) For the results of administration and management of Neolithic Humans Park, the visitors enjoyed and were impressed by the Park’s activities. They satisfied with the natural environment. About the community participation, people’s involvement was found for the plan setting in form of board committee. They were participated by 1) being organizers of the activities 2) equipment supporters 3) parking provider. The assessment was conducted by evaluation form, meeting and suggestion box. About the advantages working as organizers of the activities, the 3,380Year Neolithic Humans Park was considered as the learning center and people had the sense of belonging. 4) The effective administration and management guidelines of 3,380-Year Neolithic Humans Park were: 1) For the administrative aspect, the professional administration should be formed by appointing competent executive who had experienced on museum administration. 2) For the service aspect, the antiques should be displayed systematically by zoning according to universal standard and the guide should be stand-by for giving information to the visitors. 3) For the budget aspect, additional budget should be increased by selling souvenirs such as: keyrings, caps, T-shirt, stone hammers, etc. and 4) For the transmission of knowledge, training courses should be provided to increase the officers’ ability and skill on the administration and management of Neolithic Humans Park and the officers should have the opportunity to visit another museum. Keywords: administration, management, the Neolithic Humans Park